Distinct Sources of Deterministic and Stochastic Components of Action Timing Decisions in Rodent Frontal Cortex - Murakami, Masayoshi (2018)
Submitted by Catarina Pimentel (catarina.pimentel@research.fchampalimaud.org) on 2018-06-29T14:31:25Z No. of bitstreams: 1 Murakami et al., 2017, Neuron.pdf: 2505262 bytes, checksum: d3992b12799e62044eaa178300651b6a (MD5)